Teleseismic measurements of upper mantle shear wave anisotropy in the Isthmus of Tehuantepec, Mexico. Issue 3 (3rd August 2021) - León Soto, Gerardo; Valenzuela, Raúl W; Arceo, R; Huesca-Pérez, Eduardo; Rosas, Ricardo Vazquez
SUMMARY: Shear wave splitting measurements in the Isthmus of Tehuantepec (IT), southern Mexico, inferred from teleseismic core phases are presented. Measurements were made along a south-to-north profile across the IT. The results show a predominantly trench-normal pattern of fast polarization orientations with averaged delay times up to 2.2 s. Fast orientations near the trench suggest a corner flow in the mantle wedge and an entrained flow in the subslab region. Away the trench, fast orientations are parallel to the Absolute Plate Motion, suggesting that the anisotropy in that region is driven by a simple asthenospheric flow. A comparison with splitting measurements made in the Mexican subduction zone shows a 17° clockwise rotation of the fast orientations of between east and west Mexico. This is consistent with the observed change in orientation of 19° clockwise in the Middle American Trench (MAT). This suggests that the rotation of the fast orientations is controlled by the change of orientation in the MAT.